Self-degrading graphene sheets for tumor therapy. Issue 26 (1st July 2020) - Donskyi, Ievgen S.; Chen, Ying; Nickl, Philip; Guday, Guy; Qiao, Haishi; Achazi, Katharina; Lippitz, Andreas; Unger, Wolfgang E. S.; Böttcher, Christoph; Chen, Wei; Adeli, Mohsen; Haag, Rainer
Abstract : Enzyme-functionalized, doxorubicin-loaded, self-degradable graphene nanoplatforms show high antitumor activity, due to synergistic photothermal- and chemotherapy along with neutrophil-like activity. Abstract : Low biodegradability of graphene derivatives and related health risks are the main limiting factors for their in vivo biomedical applications. Here, we present the synthesis of enzyme-functionalized graphene sheets with self-degrading properties under physiological conditions and their applications in tumor therapy. The synergistic enzyme cascade glucose oxidase and myeloperoxidase are covalently conjugated to the surface of graphene sheets and two-dimensional (2D) platforms are obtained that can produce sodium hypochlorite from glucose. The enzyme-functionalized graphene sheets with up to 289 nm average size are degraded into small pieces (≤40 nm) by incubation under physiological conditions for 24 h. Biodegradable graphene sheets are further loaded with doxorubicin and their ability for tumor therapy is evaluated in vitro and in vivo . The laser-triggered release of doxorubicin in combination with the enzymatic activity of the functionalized graphene sheets results in a synergistic antitumor activity. Taking advantage of their neutrophil-like activity, fast biodegradability, high photo- and chemotherapeutic effects, the novel two-dimensional nanoplatforms can be used for tumor therapeutic applications.